Improving thermal and flame retardant properties of epoxy resin by functionalized graphene containing phosphorous, nitrogen and silicon elements. (December 2017) - Feng, Yuezhan; He, Chengen; Wen, Yingfeng; Ye, Yunsheng; Zhou, Xingping; Xie, Xiaolin; Mai, Yiu-Wing
Abstract: As alternative flame-retardant additive for polymers, reduced graphene oxide (RGO) is often limited by its poor interfacial compatibility with matrix. In this work, a new flame retardant, containing phosphorous, nitrogen and silicon elements was used to functionalize RGO. The wrapped flame retardant chains induced the improvement in the dispersion and compatibility of RGO in epoxy (EP) matrix. As a result, the mechanical, thermal and flame retardant properties of EP-based composites were significantly improved by adding flame retardant-functionalized RGO. The peak heat release rate, total heat release and total smoke production reduced by 34%, 14% and 30%, respectively, compared to neat resin. Based the char analyses, the enhancement in flame retardancy is attributed to the outstanding char layers with high strength and thermal stability resulting from the template effect of graphene, the charring effect of phosphorus and nitrogen elements and the enhancing effect of silicon element in grafted flame retardant chains.